THE EVALUATION OF WINTER WHEAT DEPENDING ON THE INFLUENCE OF METEOROLOGICAL FACTORS IN THE CONDITIONS OF FOREST-STEPPE ZONE - Довгаль, Г. П. (Scientific Progress & Innovations, 2017)
In the article the complex analysis of climatic factors and productivity of agro-ecosystems was made by the example of typical Forest-Steppe zones of agricultural enterprises. The studies found the correlation dependence of crop capacity of winter wheat yield of some climatic factors for the 20-year period (1997–2016). By certain mathematical models the graphics features that enable us to predict the level of productivity of various crops by the impact of climate factors were built. It is found that the most significant meteorological factors for winter wheat are rainfalls in May and June, and productive moisture reserves in the soil layer 20 cm in April and May.